Orwell’s intentional fallacy in Nineteen Eighty-Four (Altre Modernità, 2018)
The essay deals with Orwell's authorial role in Nineteen Eighty-Four and the errors that he deliberately inserted in the novel. In particular, the pattern of dates and the general distribution of weekdays in the novel are tackled.